2012
DOI: 10.1103/physrevd.86.096006
|View full text |Cite
|
Sign up to set email alerts
|

Study of beta equilibrated2+1flavor quark matter in the Polyakov-Nambu-Jona-Lasinio model

Abstract: We report a first case study of the phase diagram of 2+1 flavor strongly interacting matter in β−equilibrium, using the Polyakov−Nambu−Jona-Lasinio model. Physical characteristics of relevant thermodynamic observables have been discussed. A comparative analysis with the corresponding observables in the Nambu-Jona-Lasinio model is presented. We find distinct differences between the models in terms of a number of thermodynamic quantities like the speed of sound, specific heat, various number densities as well as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 54 publications
(54 reference statements)
0
19
0
Order By: Relevance
“…[3]. Here we shall discuss the effects of finite volume on the properties of strongly interacting matter.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…[3]. Here we shall discuss the effects of finite volume on the properties of strongly interacting matter.…”
Section: Introductionmentioning
confidence: 98%
“…[6] it has been shown that the freeze-out volume increases as the ffiffi ffi s p increases. Here the authors have estimated the freeze-out volume and found it to vary from 2000 fm 3 to 3000 fm 3 . In a very recent paper [7] the volume of homogeneity has been calculated using UrQMD model [8] and compared with the experimentally available results.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In ref. [73][74][75][76][77][78][79][80][81][82][83][84][85], the authors have discussed behavioral pattern of different observables as extracted from the PNJL model. The QCD phase structure has also been investigated for imaginary chemical potentials in ref.…”
Section: Introductionmentioning
confidence: 99%
“…Deconfined quark matter could also exist in the core of neutron stars (NS), where the density is high. The present study is expected to give us a better insight into the role that the superdense matter created in heavy ion collision experiments play in our understanding of the properties of matter inside the core of supermassive stars in the Universe (Bhattacharyya et al, 2012).…”
Section: Introductionmentioning
confidence: 99%